Business planning and entrepreneurship : an accounting approach - Kraten, Michael (New York : Business Expert Press, 2010)
'This text is a nuts-and-bolts guide to business planning. It is designed to function as a handbook for entrepreneurs who wish to apply techniques of management accounting to their planning activities.'--Back cover.
Keywords: Business planning; Entrepreneurship; Strategic planning